Resilience to Online Disinformation: A Framework for Cross-National Comparative Research. (July 2020) - Humprecht, Edda; Esser, Frank; Van Aelst, Peter
Online disinformation is considered a major challenge for modern democracies. It is widely understood as misleading content produced to generate profits, pursue political goals, or maliciously deceive. Our starting point is the assumption that some countries are more resilient to online disinformation than others. To understand what conditions influence this resilience, we choose a comparative cross-national approach. In the first step, we develop a theoretical framework that presents these country conditions as theoretical dimensions. In the second step, we translate the dimensions into quantifiable indicators that allow us to measure their significance on a comparative cross-country basis. In the third part of the study, we empirically examine eighteen Western democracies. A cluster analysis yields three country groups: one group with high resilience to online disinformation (including the Northern European systems, for instance) and two country groups with low resilience (including the polarized Southern European countries and the United States). In the final part, we discuss the heuristic value of the framework for comparative political communication research in the age of information pollution.